Tango and Enactivism: First Steps in Exploring the Dynamics and Experience of Interaction - Van Alphen, Floortje (2014)
Tango dancing is not just ethnographically interesting, but might actually provide a way to study interaction as such. An orientation to this improvisational dance as an embodied practice and experience is given. Enactivism is proposed as an adequate framework for further study. It is argued that approaching tango in terms of participatory sense-making, mutual incorporation and consensually coordinated action helps in clarifying its possible contributions to (cultural) psychology. Possible contributions such as facilitating the study of the dynamics of interaction, of intersubjectivity and of culture as joint activity.